2009
DOI: 10.1029/2009jd011978
|View full text |Cite
|
Sign up to set email alerts
|

Clear‐sky shortwave radiative closure for the Cabauw Baseline Surface Radiation Network site, Netherlands

Abstract: [1] In this paper a clear-sky shortwave closure analysis is presented for the Baseline Surface Radiation Network (BSRN) site of Cabauw, Netherlands (51.97°N, 4.93°E). The analysis is based on an exceptional period of fine weather during the first half of May 2008, resulting in a selection of 72 comparisons, on 6 days, between BSRN measurements and Doubling Adding KNMI (DAK) model simulations of direct, diffuse, and global irradiances. The data span a wide range of aerosol properties, water vapor columns, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…The analysis also shows that the average differences between empirical data and model calculations are close to results obtained by other authors in other regions (Kato et al, 1997;Henzing et al, 2004;Michalsky et al, 2006;Nowak et al, 2008;Wang et al, 2009;Halthore et al, 1998Halthore et al, , 2004Plakhina et al, 1998;Chubarova et al, 1999). It is important that our results were obtained under the conditions of high and moderate atmospheric transmittance, where the optical depth, scattering phase function, and aerosol single scattering albedo errors increase significantly.…”
Section: Results Of Complex Aerosol Experimentssupporting
confidence: 72%
“…The analysis also shows that the average differences between empirical data and model calculations are close to results obtained by other authors in other regions (Kato et al, 1997;Henzing et al, 2004;Michalsky et al, 2006;Nowak et al, 2008;Wang et al, 2009;Halthore et al, 1998Halthore et al, , 2004Plakhina et al, 1998;Chubarova et al, 1999). It is important that our results were obtained under the conditions of high and moderate atmospheric transmittance, where the optical depth, scattering phase function, and aerosol single scattering albedo errors increase significantly.…”
Section: Results Of Complex Aerosol Experimentssupporting
confidence: 72%
“…With respect to observations, by isolating the aerosol impacts on the SW radiation, Hatzianastassiou et al [2005] and Wang et al [2009] have shown that detailed aerosol temporal evolution and vertical profiles are needed to reproduce the observed direct/diffuse partitioning and global irradiance [see also Meywerk and Ramanathan, 1999;Singh et al, 2010]. The available observational campaigns studying the aerosol impacts on the troposphere [e.g., de Wekker et al, 2004;Johnson et al, 2008] focused mainly on instrument comparisons and data validation without discussing in detail how the aerosols influence the boundary-layer vertical structure and the CBL heat budget.…”
Section: 1002/2013jd021237mentioning
confidence: 99%
“…Depending on the aerosol characteristics [Liu and Ou, 1990;Wang et al, 2009], chemical composition [Yu and Zhang, 2011], and vertical distribution [Knapp et al, 2002;Raut and Chazette, 2008;Sakaeda et al, 2011], their effects on the surface radiation/energy budgets range from negligible to very significant [see also Kaufman et al, 2002;Matthias and Bosenberg, 2002;Forster et al, 2007;Arneth et al, 2010;Costabile et al, 2013]. More specifically, aerosols modify the convective boundary layer (CBL) dynamics changing its depth, vertical structure, and entrainment zone characteristics [Ackerman, 1977;Venkatram and Viskanta, 1977;Zhang et al, 2010;Barbaro et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The mean differences of modeled minus observed global SDR are small (<1%) and within the instrumental error. [2] found mean differences between model and measurements of 2 W/m 2 (+0.2%) for the direct irradiance, 1 W/m 2 (+0.8%) for the diffuse irradiance, and 2 W/m 2 (+0.3%) for the global irradiance at Cabauw (Netherlands) BSRN site.…”
Section: Introductionmentioning
confidence: 99%